STRATEGI KESANTUNAN BERBAHASA DALAM FILM ASSALAMUALAIKUM CALON IMAM - Setiyono, Tatang; Wardiani, Ririen; Setiawan, Heru (STKIP PGRI Ponorogo Press, 2021)
Language is used by human to communicate and interact each other.Due to the importance of language use in society, pragmatics become an important analysis part One of the studies in pragmatics discusses about the language politeness. This research focused on the principle of language politeness using Geoffrey Leech’s theory, six maxims, namely the tact maxim generosity maxim, Approbation Maxim, Modesty maxim, Agreemen maxim, Sympaty maxim. This study aimed to describe the strategy of language politeness in the film Assalamualaikum Calon Imam. The method used in this research was descriptive qualitative. This study decribed the principles of politeness in films. The object of study in this research was film. The data used in this study were the utterances of the main and supporting characters in the film. The research results that the six maxims were spoken by the main character and the supporting character. The conclusion of this research was that the film players obey the politeness strategy in the form of maxims. There are six maxims obeyed in the speech, namely maxim generosity maxim, Approbation Maxim, Modesty maxim, Agreemen maxim, Sympaty maxim.